M2 macrophage infusion ameliorates diabetic glomerulopathy via the JAK2/STAT3 pathway in db/db mice - Yulin Gu; Songyan Yu; Weijun Gu; Bing Li; Jing Xue; Jiejie Liu; Qi Zhang; Yaqi Yin; Haixia Zhang; Qinghua Guo; Mingxia Yuan; Zhaohui Lyu; et al. (Renal Failure)
Objectives: To explore the therapeutic effects of M2 macrophages in diabetic nephropathy (DN) and their mechanism.Methods: We infused M2 macrophages stimulated with IL-4 into 10-week-old db/db mice once a week for 4 weeks through the tail vein as M2 group. Then we investigated the role of M2 macrophages in alleviating the infammation of DN and explored the mechanism.Results: M2 macrophages hindered the progression of DN, reduced the levels of IL-1β (DN group was 34%, M2 group was 13%, p < 0.01) and MCP-1 (DN group was 49%, M2 group was 16%, p < 0.01) in the glomeruli. It was also proven that M2 macrophages alleviate mesangial cell injury caused by a high glucose environment. M2 macrophage tracking showed that the infused M2 macrophages migrated to the kidney, and the number of M2 macrophages in the kidney reached a maximum on day 3. Moreover, the ratio of M2 to M1 macrophages was 2.3 in the M2 infusion group, while 0.4 in the DN group (p < 0.01). Mechanistically, M2 macrophages downregulated Janus kinase (JAK) 2 and signal transducer and activator of transcription (STAT) 3 in mesangial cells.Conclusions: Multiple infusions of M2 macrophages significantly alleviated inflammation in the kidney and hindered the progression of DN at least partially by abrogating the M1/M2 homeostasis disturbances and suppressing the JAK2/STAT3 pathway in glomerular mesangial cells. M2 macrophage infusion may be a new therapeutic strategy for DN treatment.